Creativity - Manuel Brito, Sílvio; Fernandes Thomaz, João P. C. (IntechOpen, 2022)
What is creativity? There are many definitions, many of which involve trying different experiences, searching for new solutions, exercising our brains, and meeting and talking with new people. To be creative we need to believe in our skills and step outside our comfort zones in the search for new challenges. This book is a discussion of creativity in four parts: creativity behaviour, creativity learning, creativity in science and arts, and creativity tendencies. Chapters address such topics as creativity in children, creativity in education, creativity at the emotional level, and more.